Growing up trans [videorecording (DVD)] - Navasky, Miri; O'Connor, Karen (Film editor) (Frontline (Television program), 2015)
An intimate exploration of the struggles and choices facing transgender kids and their parents. Through moving, personal stories of children, parents, and doctors, the film examines new medical interventions increasingly being offered at younger ages.